'Africa's China': Chinese manufacturing investment in Nigeria and channels for technology transfer. Issue 4 (2nd October 2021) - Chen, Yunnan
ABSTRACT: Nigeria has been one of the primary destinations for Chinese foreign direct investment (FDI) in Africa, with emerging clusters in manufacturing sectors. FDI holds potential for technology transfer processes that can foster wider industrialization and structural transformation, but this depends on the development of local linkages that can foster positive spillovers. Through fieldwork and structured survey methods, this paper examines drivers of Chinese outward investment in Nigeria, particularly from 2014 to 2017, highlighting linkages and mechanisms of technology transfer that may catalyze transformation processes and taking a critical view of their potential. I find that, while cases of technology and skills transfer exist, investing firms face challenges of poor infrastructure, lack of skills, and low social trust, which hinder the development of linkages and industrial supply chains. In the wake of the 2014 economic recession, firms cited political and exchange rate instability as challenging; however, greater localization and building local linkages make firms better prepared to weather such challenges.